2022
DOI: 10.1371/journal.pone.0274704
|View full text |Cite
|
Sign up to set email alerts
|

HAPLN1 confers multiple myeloma cell resistance to several classes of therapeutic drugs

Abstract: Multiple myeloma (MM), a malignant plasma cell infiltration of the bone marrow, is generally considered incurable: resistance to multiple therapeutic drugs inevitably arises from tumor cell-intrinsic and tumor microenvironment (TME)-mediated mechanisms. Here we report that the proteoglycan tandem repeat 1 (PTR1) domain of the TME matrix protein, hyaluronan and proteoglycan link protein 1 (HAPLN1), induces a host of cell survival genes in MM cells and variable resistance to different classes of clinical drugs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 70 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…We previously performed RNA sequencing (RNA-seq) analysis of RPMI8226 MM cells exposed to recombinant PTR1 (GSE202672) and identified NF-κB and JAK/STAT as potentially enriched signaling pathways. 14 We previously confirmed NF-κB activation, 12 but, to our knowledge, STAT activation has not been demonstrated by stimulation of MM cells with HAPLN1 matrikine. To further assess the potential involvement of STAT factors, we also evaluated the RNA-seq data using a novel bioinformatics tool, Mining Algorithm for GenetIc Controllers 21 and, again, identified NF-κB and STAT transcription factors as being among the top potential drivers of transcriptional changes in the HAPLN1 matrikine–induced genes ( Figure 3 A; supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…We previously performed RNA sequencing (RNA-seq) analysis of RPMI8226 MM cells exposed to recombinant PTR1 (GSE202672) and identified NF-κB and JAK/STAT as potentially enriched signaling pathways. 14 We previously confirmed NF-κB activation, 12 but, to our knowledge, STAT activation has not been demonstrated by stimulation of MM cells with HAPLN1 matrikine. To further assess the potential involvement of STAT factors, we also evaluated the RNA-seq data using a novel bioinformatics tool, Mining Algorithm for GenetIc Controllers 21 and, again, identified NF-κB and STAT transcription factors as being among the top potential drivers of transcriptional changes in the HAPLN1 matrikine–induced genes ( Figure 3 A; supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 65%
“…We previously demonstrated that HAPLN1 matrikine can activate NF-κB signaling and induce NF-κB regulated drug resistance genes in MM cells. 12 , 14 This study showed peak NF-κB activation occurring within 2 hours after HAPLN1-PTR1 treatment in RPMI8226 cells, whereas peak STAT1 phosphorylation was delayed and observed 3 to 6 hours after stimulation. This temporal sequence suggests that STAT1 phosphorylation takes place after NF-κB activation.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Interestingly, decreased ITIH2 expression levels were associated with bortezomib resistance in multiple myeloma [160]. HAPLN1 induced multi-drug resistance to bortezomib and ixazomib in patients with multiple myeloma [161]. GC patients with high VCAN are often resistant to immunotherapy [149]; in one study, cervical cancer patients who were resistant to chemotherapy also presented high expression of VCAN [162].…”
Section: Deregulated Haims In Solid Tumoursmentioning
confidence: 98%